Impact of silver on fluorophosphate glasses to improve in vitro bioactivity and antibacterial efficacy. Issue 17 (1st September 2022) - Dhivya, V.; Rajkumar, G.; Mahalaxmi, S.; Rajkumar, K.; Saravana Karthikeyan, B.; Kavitha, S.; Karpagam, R.; Sakthipandi, K.; Sathishkumar, G.K.
Abstract: This article discusses the effect of silver oxide (Ag2 O) on structural changes, apatite-forming ability, and bioactivity during addition onto the fluorophosphate glass (FPG) network. The foremost objective of silver incorporation on to fluorophosphate glass is to enhance the antibacterial efficacy of glass material which can be widely used as implants to minimize the post-surgical infections. Silver-added fluorophosphate glasses (AFPGs) with composition of 48P2 O5 –29CaO−(20− x )Na2 O–3CaF2 − x Ag2 O ( x = 0, 0.3, 0.6, 0.9, and 1.2 mol%) were prepared using conventional glass-melting method followed by rapid quenching technique. The in vitro apatite-forming ability of AFPG was evaluated by immersing the samples in simulated body fluid (SBF) for 21 days. The pH variations of the SBF solution were noted throughout the in vitro study and plotted to estimate dissolution mechanism. The structural properties and compositional estimation of AFPG samples before and after in vitro study were analyzed using X-ray diffractometer, Fourier transform infrared spectroscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy, and X-ray photoelectron spectroscopy. Cytotoxicity of the prepared AFPG samples was evaluated using MTT assay. The bacteriostatic effect of AFPG samples were studied using different strains of bacteria such as Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumonia, Staphylococcus aureus, S. epidermidis, and S. mutans. The obtained peaks from XRD analysis at 28.12°, 31.73°, 46.71°, 29.11°, 32.25°, 51.59°, and 67.49° confirm crystalline nature and apatite formation on the glass surface. The attained characteristic FTIR peaks at 560 and 600 cm −1 shows the presence of apatite groups of vibration. The SEM image infers the spherical structure on the glass surface representing the presence of apatite layer and the EDAX graph shows the elemental composition of the prepared glass surface. From the present study, it was noted that glass sample containing 0.9 mol % of Ag2 O enhanced apatite formation, was less cytotoxic and showed better antibacterial activity. Thus it can be inferred that AFPG0.9 sample can play a significant role in biomedical applications.